Old enemies - Michael Dobbs (Simon & Schuster, 2011)
A global conspiracy behins in the Swiss Alps, when a teenage girl is thrown from a helicopter and her boyfriend, Ruari, is brutally abducted. Yet this is no ordinary kidnap; it is about power, not mon